Nietzsche versus nihilism. Genealogical contributions to discussion on the value of moral values - Dolewski, Robert (Hybris, 2014)
The object of this work is to show Nietzsche’s philosophical attitude towards nihilism as focused on overcoming nihilism. The way leading towards overcoming nihilism guides through criticism of moral values descended from Platonism and Christianity. Therefore, the overcoming of nihilism necessitates a moment of radical nihilism — destruction of the highest European values — resulting from undertaking the critique of moral values. Genealogy is considered here to be the main tool used by Nietzsche in his criticism — an art of interpreting the condition’s in which moral values emerge in order to determine their value with regard to human life (understood as the will to power). At the same time, the Nietzschean genealogy is considered to unfold the path towards overcoming nihilism, as it shows the ability of the human being to represent and bestow values to life — and through the category of the will to power, sets a criterion for comparison of different values in terms of their strengthening or weakening influence.